2015
DOI: 10.7554/elife.03599
|View full text |Cite|
|
Sign up to set email alerts
|

Calcium specificity signaling mechanisms in abscisic acid signal transduction in Arabidopsis guard cells

Abstract: A central question is how specificity in cellular responses to the eukaryotic second messenger Ca2+ is achieved. Plant guard cells, that form stomatal pores for gas exchange, provide a powerful system for in depth investigation of Ca2+-signaling specificity in plants. In intact guard cells, abscisic acid (ABA) enhances (primes) the Ca2+-sensitivity of downstream signaling events that result in activation of S-type anion channels during stomatal closure, providing a specificity mechanism in Ca2+-signaling. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
277
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(285 citation statements)
references
References 105 publications
(239 reference statements)
8
277
0
Order By: Relevance
“…Several studies have reported previously that the minimal core mechanisms of ABA signaling can be reconstituted in vitro, and that the core complex phosphorylates both AREB/ABFs and SLAC1 in response to ABA Brandt et al, 2012Brandt et al, , 2015. On the basis of results obtained in this study, we attempted to reconstitute the ABA signaling system including AKS1 in vitro.…”
Section: Reconstitution Of Aba-induced Aks1 Phosphorylation In Vitromentioning
confidence: 89%
“…Several studies have reported previously that the minimal core mechanisms of ABA signaling can be reconstituted in vitro, and that the core complex phosphorylates both AREB/ABFs and SLAC1 in response to ABA Brandt et al, 2012Brandt et al, , 2015. On the basis of results obtained in this study, we attempted to reconstitute the ABA signaling system including AKS1 in vitro.…”
Section: Reconstitution Of Aba-induced Aks1 Phosphorylation In Vitromentioning
confidence: 89%
“…Signal integration and modulation by parallel and interacting pathways might be centrally important in planta. Stomatal closure and ABA activation of SLAC1 in the cpk5 cpk6 cpk11 cpk23 quadruple mutant was impaired despite intact OST1, thus OST1 alone cannot complement the loss of CPKs (Brandt et al, 2015). Conversely, even though CPKs can activate SLAC1 in X. laevis oocytes, they do not substitute the loss of OST1 function in planta (Scherzer et al, 2012).…”
Section: Ros Signal Amplification In Aba-induced Stomatal Closurementioning
confidence: 96%
“…For example, CPK21 activated SLAC1 and SLAH3 currents in oocytes (Geiger et al, 2010(Geiger et al, , 2011, but the cpk21 mutant did not display impaired stomatal regulation (Merilo et al, 2013). Similarly, CPK5 activated SLAC1 currents in oocytes, but whole-cell patch-clamp studies showed that loss of CPK5 alone did not disrupt ABA activation of S-type anion channels (Brandt et al, 2015). However, channel activation and ABA-induced stomatal closure were reduced in the cpk5 cpk6 cpk11 cpk23 quadruple mutant, suggesting functional redundancy or combinatorial requirement within the CPK family.…”
Section: + -Dependent Regulation Of Rbohsmentioning
confidence: 99%
“…The phenotype of single gene mutants in the key SnRK2 for stomatal responses to ABA, OST1, are profound, displaying no sensitivity to ABA (Mustilli et al, 2002) or VPD (Merilo et al, 2013;Merilo et al, 2015). While other SnRK2-independent signaling pathways for ABA perception and SLAC activation have been suggested (Geiger et al, 2010;Brandt et al, 2012;Pornsiriwong et al, 2017), these are redundant and many either converge or require cross-talk with functional OST1 to activate anion channels (Brandt et al, 2015). Whether these alternative SnRK2-independent ABA signaling pathways play an adaptively relevant role in stomatal function is yet to be determined.…”
Section: Co-option Of An Ancient and Highly Conserved Aba Signaling Pmentioning
confidence: 99%